MSMEs Tax Reform for Financial Sustainability: Financial Literacy, Financial Capability and Capital Structure - Hartaty, Sri; Oktarida, Anggeraini (West Science Accounting and Finance, 2024)
In light of tax sector reforms, this study explores the dynamics of Micro, Small, and Medium-Sized Enterprises (MSMEs), with a particular emphasis on the impact of capital structure, financial literacy, and financial aptitude on these businesses' long-term viability. Structural Equation Modelling with Partial Least Squares (SEM-PLS) analysis was performed on a sample of 231 MSMEs. The findings show a strong positive correlation between capital structure and financial sustainability, financial literacy and capability, and financial capability and capital structure. For educators, practitioners, and policymakers looking to improve MSMEs' financial resilience in the face of changing tax sector reforms, the study offers insightful information.